2021
DOI: 10.1155/2021/8799537
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Hypogonadism in Male Persons with Diabetes Mellitus

Abstract: Aims. To characterize hypogonadism in male persons with diabetes mellitus. Patients and Methods. 184 consecutive male persons with diabetes were studied. Besides the usual care, total testosterone (TT), estradiol (E2), FSH, and LH were measured in the last appointment and in 40 patients, also in the next two appointments. Statistical analysis compared groups and explored factors for TT and LH levels. Results. TT levels were stable and highly correlated (r > 0.750, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Only a few studies have investigated the effect of metformin on testosterone concentrations. Observational, case studies and case‐control studies show conflicting results with some studies reporting a negative effect of metformin on total testosterone 29–31 , while others report a beneficial 32 or even no effect 31 . Similarly, both negative and beneficial effects are reported by observational and case (‐controlled) studies on free or bioavailable testosterone 29,31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have investigated the effect of metformin on testosterone concentrations. Observational, case studies and case‐control studies show conflicting results with some studies reporting a negative effect of metformin on total testosterone 29–31 , while others report a beneficial 32 or even no effect 31 . Similarly, both negative and beneficial effects are reported by observational and case (‐controlled) studies on free or bioavailable testosterone 29,31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged duration of metformin-based therapy reduces T levels and counteracts the T elevation accompanied by improved blood glucose[ 28 ]. Low T levels have also been observed in patients on metformin, regardless of age, duration of the disease and hemoglobin (HbA1c)[ 29 ]. A recent study indicated that for fathers who took one or more prescriptions for metformin during the development of fertilizing sperm, the likelihood of their male offspring having genital birth defects was increased[ 30 ].…”
Section: Pharmacological Management Of Obesitymentioning
confidence: 99%
“…Classifying hypogonadism in this way helps doctors choose the most effective course of therapy. Treatment for secondary hypogonadism may potentially restore fertility and normalize testosterone levels, but in primary hypogonadism, only testosterone therapy is an option, and this medication reduces fertility since it suppresses the hypothalamic-pituitary-gonadal (HGP) axis [126,127].…”
Section: Hypogonadotropic Hypogonadismmentioning
confidence: 99%